Cost-effectiveness analysis of HPV vaccination for the prevention of oropharyngeal cancer in Chinese adolescent males - Li, Jiajia; Li, Ruifeng; Qin, Ruixi; Wang, Hongyun; Wang, Di; Zhou, Liangru (Frontiers in Public Health, 2025)
BackgroundIn the context of oropharyngeal cancer poised to impose a significant disease burden, this study conducted an economic evaluation of HPV vaccination in Chinese male adolescents for the prevention of HPV-positive oropharyngeal cancer (OPC-HPV+), by constructing a multi-state Markov model from the societal perspective.MethodsThe model estimated the cost, effectiveness, and health utility of the bivalent, quadrivalent, and nonavalent HPV vaccines in preventing OPC-HPV+. Incremental cost-utility ratio (ICUR) was used to evaluate the economic viability of the vaccination strategies. One-way sensitivity analysis and probabilistic sensitivity analysis were employed to assess the model’s stability.ResultsAt a vaccine coverage rate of 70%, the incremental cost-effectiveness ratios of the bivalent, quadrivalent, and nonavalent vaccines were all lower than the per capita GDP compared to no vaccination, indicating that the vaccination strategies are highly cost-effective. The nonavalent vaccine has the highest incremental cost-effectiveness ratio, at 64,913.42 yuan ($9,211.86)/QALY. This strategy also has the highest cost, at 112.34 billion yuan, but it provides the best protection outcomes, preventing 2,545,988 cases of persistent HPV infection, 31,186 cases of OPC-HPV+, and 15,138 deaths, saving a total of 2,641,783 QALYs. Sensitivity analysis indicates that the discount rate, vaccine efficacy, HPV infection rate in the general population, and the probability of spontaneous clearance are the main factors affecting the pairwise comparison results of the strategies, which may lead to instability in the cost-effectiveness of the nonavalent vaccine.ConclusionHPV vaccination for male adolescents to prevent oropharyngeal cancer is cost-effective compared to no vaccination. China could expand the coverage of the appropriate-priced HPV vaccine to male adolescents in order to reduce the incidence of oropharyngeal cancer, improve male health quality, and protect public health.